Australian outbound student mobility : quality dimensions for international fieldwork in health sciences. - Tan, B-K; Flavell, Helen; Ferns, Sonia; Jordan, Joanne (Office for Learning and Teaching, 2015)
This is a guide to quality dimensions for international fieldwork for Australian tertiary health science students. It was produced as part of a program that aimed to improve student learning by identifying good practice in this field, establish academic standards for international fieldwork and support benchmarking. International fieldwork improves graduate work-readiness as well as Australia's engagement in the international arena. It can provide rich learning experiences that support the achievement of graduate capabilities. Utilising the Delphi method this project identified the minimum academic standards for student preparation, supervision and assessment in health sciences international fieldwork.